Long-term Treatment with Growth Hormone Decreases Plasminogen Activator Inhibitor-1 and Tissue Plasminogen Activator in Growth Hormone-deficient Adults - Johansson, Jan-Ove; Landin, Kerstin; Johannsson, Gudmundur; Tengborn, Lilian; Bengtsson, Bengt-Åke (Thrombosis and Haemostasis, 1996)
The syndrome of growth hormone deficiency (GHD) in adults is associated with premature atherosclerosis, increased cardiovascular mortality, abnormal lipoprotein patterns and abnormal body composition. We have previously shown that GH-deficient adults have increased concentrations of fibrinogen and plasminogen activator inhibitor (PAI-1) activity.The aim of the present investigation was to study coagulation and fibrinolysis in 17 patients with adult-onset GHD during two years of treatment with recombinant human GH (12 μg/kg body weight/day). The impact of the contemporary changes in metabolic variables and body composition on coagulation and fibrinolysis was studied. The patients received conventional thyroid, adrenal and gonadal hormone replacement therapy.PAI-1 activity, PAI-1 antigen and tissue plasminogen activator (t-PA) antigen levels decreased during the GH treatment period (p <0.05). The decrease was more pronounced in patients with high pre-treatment levels of the different variables. a2-antiplasmin decreased (p <0.05), while plasminogen was unchanged during two years of GH treatment.Fibrinogen concentrations tended to decrease after two years of GH treatment (p = 0.06), while the coagulation factors VII and VIII were unchanged, von Willebrand factor demonstrated a transient decrease after 18 months of GH treatment. The coagulation inhibitor, protein C, decreased (p <0.05), while antithrombin was unchanged.Fasting plasma insulin increased (p <0.01), but blood glucose did not differ after two years of GH treatment. Serum high-density lipoprotein cholesterol, total cholesterol and triglycerides were unaltered. Body fat decreased during the initial GH treatment but was unaltered after two years, while lean body mass increased (p <0.001) and the waist over hip circumference ratio tended to decrease (p = 0.06).In conclusion, PAI-1 activity, PAI-1 antigen and t-PA antigen decreased during long-term GH treatment. These changes may be a direct effect of GH itself or may be secondary to the favourable changes in body composition. It remains to be seen whether changes in these fibrinolytic variables during rhGH treatment reduces the cardiovascular risk in patients with GHD. The present results suggest that GH plays a role in the regulation of fibrinolysis.